Fortune des "Voyages de Gulliver" dans l'édition pour la jeunesse en France - Connan-Pintado, Christiane (Ondina - Ondine, 2020)
The notoriety of heritage works has the side effect of their dissemination in more accessible forms, especially when they are intended for children. Such is the fate of Jonathan Swift’s novel whose character has largely overshadowed the author. The article focuses on the French reception of Gulliver’s Travels as part of the Youth Edition. Translated from the early eighteenth century, the novel is shortened, its plot is simplified, often reduced to the first trip, and the audacity of its subject are watered down. Moreover, it is proposed in the most varied forms, at all levels of legitimacy, from illustrated novels to comics and manga. It is proposed to go through the stages of this diffusion by focusing on certain editors and some remarkable textual and iconographic reformulations.Keywords: Gulliver’s Travels, edition for youth, adaptation, legitimacy, text/image.